Ethel Mae Morgan: An African-American Biography Wabaunsee County, Kansas 1898-1989 - Reimers, Lorraine (Kansas State University. Dept. of History. Chapman Center for Rural Studies, 2010)
Lorraine Reimers examines the life of Ethel Morgan, an African American quilter and oral historian from Wabaunsee County. Throughout her long life, in which she raised a large family and clothed them all by hand, Ethel Morgan strove to preserve the stories of African American settlers. She was known and loved for her beautiful quilts, exceptional home canning, devotion to the Beecher Bible and Rifle Church, and her local history knowledge. The author includes photographs of Ethel Morgan and her quilts.
Keywords: African American; Wabaunsee County; Beecher Bible and Rifle Church; Quilts